Kontribusi Komitmen Kerja dan Iklim Sekolah terhadap Kepuasan Kerja Guru SMA Kecamatan IV Jurai Pesisir Selatan - Muhammad Sahnan; Mahyudin Ritonga (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2018)
This study aims to explore the contribution of work commitments and school climate on teacher’s job satisfaction. This research uses correlational methods that were analyzed with correlation and regression techniques. The result showed that work commitments was contribute significantly to job satisfaction of teachers. This means that the work commitments could be used as a predictor for the teacher’s job satisfaction. Then school climate contribute significantly to teacher’s job satisfaction also. This results means that the school climate can be used as a predictor for the teacher’s job satisfaction. Commitment to work and school climate were contribute significantly to teacher’s job satisfaction. Teacher’s job satisfaction is influenced by work commitments and school climate, either individually or jointly. Further, high commitment and also supported by a school climate create the conducive and improve the teacher’s job satisfaction. Commitment to work and school climate are two factors which are very important because it can affect the job satisfaction, but there are other factors that are believed to take effect on teacher’s job satisfaction.